Research of marketing effectiveness of the enterprises of oil and gas complex of Ukraine - Перевозова, Ірина Володимирівна; Устенко, Андрій Олександрович; Малинка, Оксана Ярославівна (Technology audit and production reserves, 2016)
It is researched that most enterprises of oil and gas complex don’t pay attention to the effective usage of marketing concepts, and this leads to a utilitarian approach towards management and solving of short-term problems. However, using marketing technologies in the production of oil and gas sector will not only prevent strategic mistakes, but also define the most effective and promising areas of the industrial sector that will contribute to the ultimate positive systematic effect in the link: enterprise – industrial sector – the economy of Ukraine. The main drawbacks of marketing organization performance of «Naftogaz of Ukraine» are defined, namely the lack of a definite positioning in the domestic and foreign markets; the dependence on the world market prices; the lack of an effective marketing strategy; low level of monitoring and marketing auditing as separate management functions, and within total controlling of an enterprise. In order to develop an effective marketing strategy for the enterprises of oil and gas complex, and to monitor market efficiency and manage market position, it is suggested to complete financial performance indicators with marketing efficiency indexes. It is substantiated that a standardized methodology of external market activity indicators estimation don’t exist, but the combination of internal and external estimate will enable management personnel and business owners to conduct a comprehensive estimation of a particular company estimation and of «Naftogaz» as a whole.